PENGARUH REAL LABORATORY DAN VIRTUAL LABORATORY TERHADAP PEMAHAMAN KONSEP PESERTA DIDIK DENGAN KEMAMPUAN AWAL BERBEDA PADA MATERI KESETIMBANGAN KIMIA - Mawadur Rohmah; Suhadi Ibnu; Endang Budiasih (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
Chemical equilibrium is one of the chemistry topics, that are considered difficult concepts, so that are needs to be delivered using the right model and learning media, one of them is learning cycle 5E model implemented with tehe real laboratory and virtual laboratory. This study aims to find out the differences of student’s conceptual understanding using learning cycle 5E model with real laboratory and virtual laboratory based on the different prior knowledge in chemical equilibrium topic. This study used quasi experimental design with Factorialized (2x2) Version of Non-equivalen Design using availability sampling technique. The samples were 11th grade students of science class 4 (real laboratory) and the 11th grade students of science class 5 (virtual laboratory). The instruments are consisting of lesson plan and learning material (treatment instruments) and student’s conceptual understanding test (measuring instruments). The data analysis was performed by Two Way Anova. The result of the study show that there are no differences in students conceptual understanding between the students who have high prior knowledge and the students who have low prior knowledge. However, students conceptual understanding who have high prior knowledge who learned using real laboratory has higher score than the students who learned using virtual laboratory. Meanwhile, students conceptual understanding who have low prior knowledge who learned using virtual laboratory has higher score than the students who learned using real laboratory.